SIGECAH as a tool for the collaborative learning of Social Sciences in Andalusian Secondary Schools - Cuesta, Ángel Ignacio Aguilar (European Journal of Geography, 2017)
Almost a decade ago, as a result of the initiative promoted by the researcher Laura García Juan, the project SIGECAH (Historical Cadastre Managing System) was born with the aim of improving the analysis of geohistorical sources from cadastral documentation, firstly in Spain, and later taking another geographical scope. Its development and efficiency have diversified it inside the educational and research sector due to its digital platform. In order to make knowledge accessible and to turn students into active agents inside the classrooms of Andalusian Secondary Schools, we present an open didactical proposal for the Social Sciences: Geography and History. Thereby, SIGECAH does not only work as a tool for the treatment of the geohistorical sources and its cartographic transformation thanks to the Geographic Information System, furthermore, because of collaborative learning, teachers and pupils can join the project from their centres of Secondary Education, sharing information and researching about the changes in different places of the Andalusian territory.